1996
DOI: 10.1039/fd9960500295
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption on a polar oxide surface: O2, C2H4and Na on Cr2O3(0001)/Cr(110)

Abstract: A polar Cr,0,(0001) surface is prepared as an epitaxial film on a Cr(ll0) substrate. The film is thick enough to represent the bulk surface. Applying a variety of surface sensitive techniques [thermal desorption spectroscopy (TDS), reflection absorption infrared spectroscopy (RAIRS), electron energy loss spectroscopy (EELS) and photoelectron spectroscopy (PES)] we have studied adsorption of molecular oxygen, ethene and sodium. ExperimentalA chromium oxide film with (0001) orientation was grown on a Cr(ll0) sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 79 publications
7
42
0
Order By: Relevance
“…Studies using isotopically labeled oxygen species, however, reveal some aspects of oxygen chemistry on oxide surfaces, in particular, the intermixture of oxygen from the gas phase and oxygen in the oxide lattice [32]. In investigations on the Mars -van Krevelen mechanism those studies play an important role.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using isotopically labeled oxygen species, however, reveal some aspects of oxygen chemistry on oxide surfaces, in particular, the intermixture of oxygen from the gas phase and oxygen in the oxide lattice [32]. In investigations on the Mars -van Krevelen mechanism those studies play an important role.…”
Section: Resultsmentioning
confidence: 99%
“…However, if the surface is reduced the situation changes considerably. We note that, different from Cr 2 O 3 (0001) [28], where we encountered a similar structural situation, the vanadyl groups cannot be reduced thermally without destroying the surface structure [16,19]. In fact, it is necessary to electron bombard the surface to selectively remove the vanadyl oxygen atoms as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18][19] In fact, it has been shown that the surface polarity can be healed by nonstoichiometric reconstructions, metalization of the surface layer, or by absorption of charged species. Furthermore, metal-oxide interfaces may have a role in stabilizing polar surfaces.…”
Section: Introductionmentioning
confidence: 99%